2013
DOI: 10.4103/0976-500x.107692
|View full text |Cite
|
Sign up to set email alerts
|

An unusual cause of cardiac arrest in a hospitalized patient

Abstract: We present an unusual case of 24 year old male who was hospitalized for dental procedure and developed cardiac arrest 2 days after the procedure. The patient presented with swelling of buccal cavity for which a biopsy was taken. Two days after the procedure, apparently normal patient suddenly presented at mid night with VT and VF, which were intractable requiring multiple DC shocks. During this period arterial blood gas analysis revealed severe acidosis. The circumstances led us to suspect poisoning as one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…They concluded that some poison, perhaps from a hand sanitizer, had triggered the peculiar anaphylactic reactions. Suspecting the role of potential toxins in this case, doctors found that a commonly used hand sanitizer had perfume added to Isopropyl alcohol and glycerine 27 . In a study of 256 Turkish university students regarding barriers to sleep, as much as 53.1% mentioned 'room scents (sweat, perfume, humidity, naphthalene, etc.)'…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that some poison, perhaps from a hand sanitizer, had triggered the peculiar anaphylactic reactions. Suspecting the role of potential toxins in this case, doctors found that a commonly used hand sanitizer had perfume added to Isopropyl alcohol and glycerine 27 . In a study of 256 Turkish university students regarding barriers to sleep, as much as 53.1% mentioned 'room scents (sweat, perfume, humidity, naphthalene, etc.)'…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cases describing intoxication from intentional ingestion of ethanol-or isopropanol-containing hand sanitizers have been reported in the literature. These have occurred in a variety of settings, including emergency rooms, 5,9,10 general hospital rooms, 3,7,[11][12][13][14][15] prison, 16 and acute psychiatric or inpatient substance abuse units. [17][18][19][20] Emadi and Coberly 13 described the case of a patient who was admitted for chest pain who became hypotensive with altered mental status.…”
Section: Discussionmentioning
confidence: 99%
“…13 He recovered from the intentional ingestion with supportive care including vasopressors and IV fluids. 13 Shetty et al 12 described a case of isopropanol ingestion in a hospitalized 24-year-old man who developed ventricular tachycardia and fibrillation with severe metabolic acidosis. Isopropanol concentrations were not listed in this case, but his gastric lavage revealed the presence of isopropanol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stevens and Hix also described a female patient admitted in hospital with underlying psychiatric illness who was later shifted to ICU in a critical condition after consuming hand sanitizer containing IPA along with some other unknown intoxicants [23]. Death of a 24 years old person was described by Shetty et al after consuming sanitizer containing IPA [39]. Another 29 year old male chronic alcoholic with a history of depression was also brought to hospital after ingesting liquid hand sanitizer.…”
Section: Global Scenario Of Abusementioning
confidence: 99%